Genetic Predisposition Of M2 Annexin A5 Haplotype In Recurrent Pregnancy Loss Among The Malays In Malaysia - Ang, Kai Cheen (2018)
Repeated Pregnancy Loss (RPL) is a prevalent condition where conventional hereditary thrombophilia factors have been ruled out in Malaysia population. M2/ANXA5 haplotype, a variation at the core promoter region of Annexin A5 (ANXA5) gene, was suggested to be a predisposition factor for RPL. ANXA5 is a placenta anticoagulant protein which binds on the surface of syncitiotrophoblasts to prevent thrombotic events that would lead to RPL. In this study, the prevalence of M2/ANXA5 haplotype was 42.2% in Malay population and 34.9% for parous controls. When compared M2/ANXA5 clinically defined primary and secondary RPL carriers to M2/ANXA5 carriers in random populations, odds ratio of 1.52 (95% CI:1.1 to 2.1) was determined.